Pengembangan Model Pengelolaan Klaim BPJS Kesehatan Rawat Inap di RSUD Kota Kendari - Asrul, Muhamad; Thamrin, Hilma Yuniar (Jurnal Ilmiah Global Education, 2025)
To improve health services in Indonesia, the government established the Social Security Organizing Agency (BPJS) which is tasked with organizing the National Health Insurance (JKN) for all Indonesian citizens. The problem that occurs at Kendari City Hospital is that there are still many claims that experience payment delays. The large number of delays in payment of claims submitted by Kendari City Hospital to BPJS health that occur every month will certainly affect the operational costs of the hospital. This study aims to determine the development of an inpatient BPJS Health claim management model at Kendari City Hospital. The research design uses a qualitative approach to identify problems and find solutions to solve obstacles to submitting inpatient claims. This research was conducted at Kendari City Hospital and BPJS Kesehatan Kendari branch with a total of 16 informants. The sampling technique used in this study was purposive sampling, the criteria for informants in this study were officers who had understanding or knowledge and were directly involved in completing the inpatient claim file documents. The results of this study indicate that by adding the stages of the medical internal verifier process as a controlling phase in the process of observing the implementation of all BPJS inpatient claim management activities to ensure that all stages of the inpatient claim management model carried out run in accordance with predetermined coding rules. The internal medical verifier has an advantage because it is a strength in claims management, as a good communication negotiator between the hospital internal verifier and BPJS Health aims to find solutions that are acceptable to the Kendari City Hospital as a service provider and BPJS Health as a patient service guarantor.